The Student Worksheet Based on PBL Model to Develop Critical Thinking Skills in Phase A: Lembar Kerja Siswa Berbasis Model PBL untuk Mengembangkan Keterampilan Berpikir Kritis Tahap A - Fatkhur Rohman; Jody Setya Hermawan; Mia Azzahra; Handoko; Yoga Fernando Rizqi (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2024)
Mathematics is a subject that uses critical thinking skills in logical reasoning. This research was conducted on grade II students of SDN 1 Sukaraja, control class 24 students and experimental class 27 students. This research and development (R&D) study adopted the 4D model and reached only the third stage (define, design, develop). The product that was developed is a student worksheet that is based on the Problem-Based Learning (PBL) model. The goal is to train students' critical thinking skills. The developed student worksheet based on PBL model is proven to be "Very Valid" based on validator's evaluation and "Very Practical" based on practicality evaluation results, so it can be used as teaching material to support learning process to train students' critical thinking skills.